A COMPARATIVE STUDY OF ROLES PLAYED BY ALUMINUM TRIBROMIDE AND ALUMINUM ACETYLACETONATE ON THE THERMAL DEGRADATION OF PMMA BY SIMULTANEOUS THERMOANALYTICAL TECHNIQUES - Arshad, M.; Masud, K.; Arif, M.; Rahman, S.; Chohan, Z. H.; Arif, M.; Qureshi, A. H.; Saeed, A.; Salma, U.; Awan, M. S. (The Nucleus, 2020)
Blends of poly(methyl methacrylate) (PMMA) were prepared with aluminum tribromide (AlBr3) and aluminum acetylacetonate (Al(acac)3)in definite ratios. Thermal studies (TG-DTG-DTA) of polymer and blends with both additives were carried out in inert atmosphere to investigate the mode of degradation and the effects of stability/destability on either component. The addition of compounds in polymer resulted early decompositions. The intermediates formed during decomposition were also identified. The possible explanation of the thermal degradation reactions is advanced on the basis of results gathered. The apparent activation energy (Eo) and order of reaction (n) of the pyrolitic reactions were determined by Horowitz and Metzger method from the corresponding TG curves.